JAMINAN HUKUM BAGI TENAGA KERJA YANG TERKENA PEMUTUSAN HUBUNGAN KERJA (PHK) AKIBAT PERUSAHAAN PAILIT - Husniyah, Husniyah; Mariana, Dina; Ridani, Ahmad; Munawarah, Desi; Husna, Raudatul; Padilah, Akhmad Nor; Habibie, Ramadhani Alfin (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
In early 1977, Indonesia faced significant difficulties in its development, triggered by the collapse of the government and the global monetary crisis. Until now, the impact of the economic crisis continues to be felt, especially in industrial life which is filled with losses and layoffs as a company survival strategy. This issue of layoffs, especially when companies go bankrupt, becomes an important focus, involving labor rights which continue to be threatened. The resilience of the power between labor and employment news is revealed in the ongoing recognition of Labor Day, demanding fairer working conditions. Even though there are regulations regarding layoffs, weak law enforcement is a serious obstacle. The era of globalization and industrial growth adds to the complexity of employment problems, especially in Indonesia with a high number of workers and the potential for layoffs. Factors triggering layoffs are very diverse, including globalization, economic transformation, and company bankruptcy. In this context, the Job Creation Law (UU CK) introduced significant changes, but also received criticism. This research focuses on the provisions for layoffs resulting from bankrupt companies in the CK Law, exploring the regulatory basis, legal protection for laid-off workers, and mechanisms for resolving their rights. The research method used is normative legal research, with a detailed explanation of the basis for layoff arrangements, legal protection for workers, and mechanisms for resolving workers’ rights in the context of bankrupt companies. This research aims to provide a comprehensive understanding of the problem of layoffs due to bankrupt companies, analyzing related provisions of the CK Law, and provides an overview of the legal protection provided to workers. It is hoped that the results of this research can contribute to policy development and improvement of labor rights protection in the context of company bankruptcy in Indonesia.